2006
DOI: 10.1002/ajh.20475
|View full text |Cite
|
Sign up to set email alerts
|

Transformation and progression of Waldenström's macroglobulinemia following cladribine therapy in two cases: natural evolution or iatrogenic causation?

Abstract: We report two cases of Waldenströ m's macroglobulinemia with an unusual aggressive transformation following treatment with cladribine (2-chlorodeoxyadenosine, 2-CdA), a purine analogue. The first patient developed transformation to a diffuse large-cell nonHodgkin lymphoma, while the second developed extensive extramedullary involvement. Both patients displayed rapid progression following transformation and were refractory to chemotherapy. Both patients were pretreated with multiple courses of prednisone and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 11 publications
0
13
0
1
Order By: Relevance
“…Follow-up started at diagnosis and ended at the date of last news or date of death, and the median follow-up for all patients was 5 years. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] The primary end point of the study was the occurrence of a secondary malignancy, either t-MDS/AML or histologic transformation to aggressive NHL, and was calculated as a cumulative probability or as a cumulative incidence of secondary events. Cumulative probability was calculated using the Kaplan-Meier estimate in which the data of patients who died were censored and in which curves were compared using the log-rank test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Follow-up started at diagnosis and ended at the date of last news or date of death, and the median follow-up for all patients was 5 years. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] The primary end point of the study was the occurrence of a secondary malignancy, either t-MDS/AML or histologic transformation to aggressive NHL, and was calculated as a cumulative probability or as a cumulative incidence of secondary events. Cumulative probability was calculated using the Kaplan-Meier estimate in which the data of patients who died were censored and in which curves were compared using the log-rank test.…”
Section: Discussionmentioning
confidence: 99%
“…4 Transformation events have been occasionally reported in WM, either without identified etiology 5,6 or after treatment with nucleoside analogs or chlorambucil. [7][8][9][10] An increased incidence of therapy-related myelodysplastic syndrome/acute myeloid leukemia (t-MDS/AML) has also been reported with the use of chemotherapeutic agents, such as anthracyclines and alkylating agents in NHL. 11 A higher than expected incidence (1.2%) of t-MDS/AML has also been reported in patients with CLL after treatment with fludarabine and chlorambucil.…”
Section: Introductionmentioning
confidence: 99%
“…The question remains as to whether a ''subclinical'' lymphoma was actually present and/or its development can be accelerated by available therapies. 34 Different therapies have been evaluated, but there is no effective therapy available yet for these RCD II patients. 2 11-17 Reports claiming good response are difficult to interpret due to an absence of clear distinction between RCD I and RCD II in these series.…”
Section: Discussionmentioning
confidence: 99%
“…This case appeared to arise in a clonally-unrelated B-cell population [8]. The rapid development of DLBCL following purine analogue therapy has been reported by others in WM although EBV was not implicated in these cases [9,10]. The overall incidence of EBV-associated DLBCL in WM is unclear although it is interesting to note that in an analysis of 92 patients with WM Lin et al demonstrated large cell transformation in 10 but failed to demonstrate evidence of EBV in 8 cases assessed by in situ hybridisation [7].…”
mentioning
confidence: 55%